Parental Grief and Marital Issues Aftermath: A Pilot Study - Mohamed Hussin, Nur Atikah; Azman, Azlinda (Maryland Institute of Research, Center for Socio-Economic Research, 2016)
The death of a child is difficult to the bereaved parents. Literature had associated the loss with marriage disruption. The issues on that the difficulties to communicate, gender-related coping mechanisms and sexual need were discussed as reasons for bereaved parents to have conflict in their relationship. However there is limited knowledge about this issue. A pilot study has been conducted among six bereaved parents. The bereaved parents were Malaysian Muslim bereaved parents. They were interviewed individually to explore the challenges or conflicts that they had experienced after the death of their child. This study revealed that there were situations which bereaved parents described as having difficulties in their relationship. However, this study also revealed that the mutual understanding and respect to each other are the most of important components for bereaved parents to maintain their relationship post-loss. This study suggested the importance of suggesting couple counselling to bereaved parents after the death of their child.